Let's Buy With Social Commerce Platforms Through Social Media Influencers: An Indian Consumer Perspective - Alam, Faizan; Tao, Meng; Lahuerta-Otero, Eva; Feifei, Zhao (Frontiers in Psychology, 2022)
The COVID-19 pandemic has had a substantial impact on the retail industry around the globe, including in the vast market of India. The response to the pandemic required stores to close and develop new ways to approach shoppers more efficiently. The worldwide usage of social media enabled the growth of social commerce (s-commerce). Influencers on s-commerce platforms use live broadcasting on their channels to promote endorsed products. The features of s-commerce influencers enhance users’ trust in the online community and s-commerce intention, impacting their online purchasing intentions. In this study, we collected data from 379 Indian consumers to test the measurement and structural model using Partial Least Square-Structural Equation Modeling (PLS-SEM) to verify our conceptual framework. We found that trust in the online community and s-commerce intention are antecedents of online purchase intentions. Additionally, the results demonstrate that trust in Indian social media influencers and s-commerce intentions are vital for boosting consumers’ purchase intention, verifying the hypothesised mediating effect of these factors. Based on these results, we suggest several managerial actions that could enhance the value of s-commerce for franchises, executives, e-retailers, and e-marketplaces.